Pengaruh ESG Disclosure dan Kinerja Lingkungan terhadap Tax Avoidance pada Perusahaan Manufaktur BEI - Magfirah Wahyu Ramadhani (ISAS, 2026)
This study aims to examine the effect of ESG disclosure and environmental performance on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange during the 2021-2024 period. This issue is important because tax avoidance may reduce corporate contributions to state revenue, while ESG practices and environmental performance have become increasingly relevant in assessing corporate accountability. The novelty of this study lies in combining ESG disclosure as an internal transparency measure and PROPER rating as a government-based environmental performance measure in the context of Indonesian manufacturing companies. This study employs a quantitative approach with an explanatory-causal design. The data used are secondary data obtained from annual reports, sustainability reports, financial statements, and PROPER ratings. The sample consists of manufacturing companies observed during the 2021-2024 period, selected using purposive sampling. The research instrument includes a documentation sheet and an ESG disclosure checklist. Data were analyzed using multiple linear regression with SPSS. The results show that ESG disclosure has a negative and significant effect on tax avoidance, with a significance value of 0.006; thus, the first hypothesis is accepted. In contrast, environmental performance has a positive and significant effect on tax avoidance, with a significance value of 0.023; therefore, the second hypothesis is rejected. These findings indicate that ESG transparency may reduce tax avoidance, while environmental performance does not necessarily reflect stronger corporate tax compliance. Keywords: ESG disclosure, environmental performance, ESG reporting, Effective tax rate, Corporate sustainability.